2013
DOI: 10.1155/2013/512103
|View full text |Cite
|
Sign up to set email alerts
|

The Enigmatic Cytokine Oncostatin M and Roles in Disease

Abstract: Oncostatin M is a secreted cytokine involved in homeostasis and in diseases involving chronic inflammation. It is a member of the gp130 family of cytokines that have pleiotropic functions in differentiation, cell proliferation, and hematopoetic, immunologic, and inflammatory networks. However, Oncostatin M also has activities novel to mediators of this cytokine family and others and may have fundamental roles in mechanisms of inflammation in pathology. Studies have explored Oncostatin M functions in cancer, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
234
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(235 citation statements)
references
References 268 publications
(289 reference statements)
0
234
0
1
Order By: Relevance
“…14,19,29,31,34,78,[80][81][82][83][84][85][86] We propose that the elevated OSM expression levels observed in cancerous tissues is an extension of the inflammatory environment initially created during the early stages of transformation as a means to suppress tumorigenicity. There is mounting evidence that OSM in the TME contributes to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…14,19,29,31,34,78,[80][81][82][83][84][85][86] We propose that the elevated OSM expression levels observed in cancerous tissues is an extension of the inflammatory environment initially created during the early stages of transformation as a means to suppress tumorigenicity. There is mounting evidence that OSM in the TME contributes to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…OSM binds 2 receptor complexes: type I, composed of gp130 and LIF receptor subunits (31), and type II, composed of gp130 and OSM receptor (OSMR) subunits (32). OSM is secreted by hematopoietic cells, such as monocytes, macrophages, dendritic cells, T cells, or neutrophils (33)(34)(35), but also by osteoblasts, osteocytes, and microglia (36)(37)(38). Its secretion is increased upon stimulation by LPS, GM-CSF, or prostaglandin E2 (34,35,37,39).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the molecular phenotype can be altered through the actions of single master regulators such as FOXA1 and ELF5 (Bernardo et al 2010, 2013, Kalyuga et al 2012, and that approximately 10% of triple-negative tumours (clinically negative for ESR1, progesterone receptor (PGR) and ERBB2) manifest luminal-like gene expression profiles (Creighton et al 2006, Bertucci et al 2012. Downregulation of the transcription factor and chromatin remodelling factor FOXA1 results in downregulation of ESR1 in MCF7 cells (Bernardo et al 2010).…”
Section: Loss Of Esr1 In Breast Cancermentioning
confidence: 99%
“…Results of studies of OSM using mouse mammary tumour models have indicated that OSM contributes to increased lung and bone metastasis (Bolin et al 2012, Guo et al 2013. Results of analyses of human tumours to date indicate that an increase in OSM and/or OSMR occurs in relationship with tumour progression in multiple tumour types including breast and cervical cancer and that this may be associated with adverse outcome (Royuela et al 2004, Garcia-Tunon et al 2008, West et al 2012, Richards 2013). …”
Section: Osm: a Key Driver Of Inflammation-mediated Suppression Of Ermentioning
confidence: 99%